Interactive TV technology and markets - Srivastava, Hari Om (Artech House digital audio and video library., 2002)
"This forward-looking book focuses on interactive television (ITV), and illustrates how it is changing the face of TV broadcasting. The book provides professionals with important technical, strategic, and creative expertise to help in the development of ITV systems and with the assessment of their future business potential. Interactive TV Technology and Markets explains how bandwidth limitations associated with analog TV signals are eliminated as cable, satellite, and terrestrial TV network operators switch to digital bandwidth."--Jacket